Autumn fish diversity in Xiamen coastal waters based on environmental DNA technology and bottom trawling - Chunyan Xu; Tongjin Wu; Chao Ma; Zhidong Zhuang; Yong Liu; Jiandi Cai; Shaoqing Xie (Environmental Biology of Fishes, 2026)
Xiamen coastal waters are rich in biological resources, with high fish diversity, which is critical for the ecological balance and fishery development. Bottom trawling is a traditional fish resource survey method, but recently, environmental DNA (eDNA) technology has also emerged. This study investigated fish diversity in the coastal waters of Xiamen during autumn using eDNA technology and bottom trawling, comparing the two methodologies. Through sampling and analysis across 13 survey stations, 134 fish species were detected based on eDNA and 75 species were captured via bottom trawling, with a combined total of 163 species belonging to 17 orders, 66 families, and 114 genera. eDNA technology significantly enhanced species detection rates (82.2% of total fish species) compared to bottom trawling (46.0%), enabling the identification of 88 additional species and demonstrating a clear advantage in detecting fish species richness. Alpha diversity analysis indicated that the average Margalef richness index derived from eDNA was significantly higher than that from bottom trawling. However, bottom trawling yielded higher Shannon, Simpson, and Pielou evenness index values compared to eDNA, with the difference in evenness being highly significant. This disparity was likely due primarily to the overwhelming dominance of Johnius belangerii in eDNA detections, which led to reduced community evenness. Beta diversity analysis showed that both methods revealed spatial heterogeneity in the fish community composition among stations. This study demonstrated that combining eDNA technology with traditional bottom trawling provides a more comprehensive assessment of fish diversity, offering a more robust scientific basis for marine ecological monitoring and conservation.